Walter Carlsnaes, Energy Vulnerability and National Security. The Energy Crises, Domestic Policy Responses and the Logic of Swedish Neutrality, London: Pinter Publishers, 1988, 136 s., £ 24,00. - Petersen, Nikolaj (Politica, 1989)
-